Community-Based School Management Model Development in The Digital Era - Andari, Shelly; Roesminingsih, Erny; Trihantoyo, Syunu (National Dong Hwa University, 2024)
This research is research that aims to develop a Community-Based School Management Model in the Digital Age. This study aims to develop a community participation model in education involving people or groups both at the implementation planning, evaluation, utilization of results, accountability and development in the education sector. In management science, the term participation is defined as a process of mental and emotional involvement in an activity. This study used research and development method to develop a well-adapted model to be integrated in primary schools for Indonesian context. A special model is needed in community-based school management to face challenges in the digital era. This model answers the gaps that occur related to school needs and community involvement in it as an effort to improve the quality of education, focusing on social demands to education output and outcome. Previously, it can be inferred from some studies that community-based management were not integrated optimally while stakeholders perceived school as a formal institutions rather than an important institution for culture, economics, knowledge to be developed. The newest model of school management was integrated on SDS Plus Al-Qodiri. It resulted on the Community-Based School Management Model in the Digital Age can be used as a guide for schools, not only partner schools but other schools with the same focus, to continue to adapt and respond to current challenges, especially in involving the community in the advancement of education.